The Relevance Of Hifdzun Nafs With The Law of Qishash: An Analysis Of Ibnu 'Ashur's Interpretation In Tafsir al-Tahrir Wa al-Tanwir - Annisaa Tusakdia; Lukman Nul Hakim; Zulfikar, Eko (CV. Doki Course and Training, 2024)
This article aims to determine the relevance of hifdzun nafs to the law of qishash from Ibn ‘Asyur’s perspective in the tafsir al-Tahrir wa al-Tanwir. Ibn ‘Asyur himself was famous as a mufasir who focused on Maqashid al-Syari’ah so that he also expressed the results of his thoughts about Maqashid in the form of interpretation. By using qualitative methods, pure literature research, this article concludes that according to Ibn ‘Asyur, qishash functions to protect human life, because with qishash people are afraid of committing murder. If a person knows that he will survive death, he will dare to commit murder in the hope that the punishment will be light. Therefore, the qishash law that was implemented has strong relevance to hifduzn nafs, namely avoiding bloodshed as in the case of the murders that occurred during the Jahiliyyah era, which resulted in the loss of many lives. The qishash law is one way to protect the soul (hifdzun nafs), by punishing people who commit murder and other criminal acts, with appropriate punishments for the benefit and survival of humans.